2015
DOI: 10.3390/ijerph13010091
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Characteristics among Housing Adaptation Clients in Sweden—Relationship to Participation and Self-Rated Health

Abstract: The aim of the paper was to explore the heterogeneity among housing adaptation clients. Cluster analysis was performed using baseline data from applicants in three Swedish municipalities. The analysis identified six main groups: “adults at risk of disability”, “young old with disabilities”, “well-functioning older adults”, “frail older adults”, “frail older with moderate cognitive impairments” and “resilient oldest old”. The clusters differed significantly in terms of participation frequency and satisfaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
(77 reference statements)
0
10
0
1
Order By: Relevance
“…A potential explanation might be that their expectations on life in general are similar to others in the same age, but when comparing their own life with others they feel much more restricted and impacted by their activity restrictions, in this study demonstrated by their higher level of ADL dependence, and thus perceive their health as lower. When it comes to the older age group, they might perceive their activity limitations and dependence as a natural consequence of ageing, and thus it has less impact on their self-rated health compared to those that are younger [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A potential explanation might be that their expectations on life in general are similar to others in the same age, but when comparing their own life with others they feel much more restricted and impacted by their activity restrictions, in this study demonstrated by their higher level of ADL dependence, and thus perceive their health as lower. When it comes to the older age group, they might perceive their activity limitations and dependence as a natural consequence of ageing, and thus it has less impact on their self-rated health compared to those that are younger [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…UIMH has been tested for validity and reliability [ 27 ], and a further validation is currently ongoing [ 28 ]. Three aspects of usability have been identified; “Self-care aspects” (compromising 5 items: going to the toilet, personal hygiene, preparing meals, preparing snacks, and moving around the home with/without a mobility device, score 5–25 points), “Social aspects” (compromising 3 items: socializing with family and friends in the home, contacting others via telephone/Skype, and watching TV/listening to radio, score 3–15 points) and “Leisure/outdoor aspects” (compromising 3 items: entering the house, picking up the mail, and engaging in hobbies and leisure activities in the home, 3–15 points) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…People applying for an HA have different ages and levels of cognitive and physical function (Kim, Ahn, Steinhoff, & Lee, 2014;Thordardottir, Chiatti, Ekstam, & Malmgren F€ ange, 2016). They often have a reduced ability to perform activities (Johansson, Lilja, Petersson, & Borell, 2007;Petersson, Kottorp, Bergstrom, & Lilja, 2009;Petersson, Lilja, & Borell, 2012;Petersson, Lilja, Hammel, & Kottorp, 2008); their functional capacity is too low to overcome the environmental barriers in their own home, and thus they become dependent on others.…”
Section: Introductionmentioning
confidence: 99%